Home price expectations and behavior: Evidence from a randomized information experiment - Luis Armona; Andreas Fuster; Basit Zafar (Federal Reserve Bank of New York, 2016)
Home price expectations are believed to play an important role in housing dynamics, yet we have limited understanding of how they are formed and how they affect behavior. Using a unique "information experiment" embedded in an online survey, this paper investigates how consumers' home price expectations respond to past home price growth and how they impact investment decisions. After eliciting respondents' initial beliefs about past and future local home price changes, we present a random subset of the respondents with factual information about past (one or five-year) changes and then re-elicit expectations. This unique "panel" data allows us to identify causal effects of the information and provides insights on the expectation formation process. We find that, on average, year-ahead home price expectations are revised in a way consistent with short-term momentum in home price growth, though respondents tend to underpredict the strength of momentum. Revisions of longer-term expectations show that respondents do not expect the empirically occurring mean reversion in home price growth. These results are consistent with recent behavioral models of housing cycles. Finally, we present robust evidence of home price expectations impacting (actual and intended) housing-related behaviors, both in the cross section and within-individual.
Keywords: D84; G11; R21; 330; housing; expectation formation; information; updating